KEDUDUKAN NOTARIS/PPAT YANG DIKENAI TPPU DAN PEMALSUAN TERKAIT AKTA YANG DIBUATNYA.(Studi Putusan No. 248/Pid.B/2022/PN.Jkt.Brt) - Irham Akbar; Hasim Purba, Suprayitno (JOURNAL OF LAW AND NATION, 2025)
Notary / PPAT is an official authorised by law to make authentic deeds, and the duties and responsibilities of the position held must be in accordance with the applicable provisions in accordance with the rules in the law, and if a Notary / PPAT violates these provisions, it can be subject to civil, criminal and administrative sanctions. Administrative sanctions include written warnings, temporary dismissal, honourable dismissal, and dishonourable dismissal, which are adjusted to the offence committed by the Notary/PPAT itself. The problems discussed in this thesis are, Why a Notary/PPAT can be subjected to the Crime of Money Laundering (TPPU) and/or the Crime of Forgery related to the deed he/she makes, then what legal consequences can be given/imposed on a Notary/PPAT who commits the Crime of Money Laundering (TPPU) and/or the Crime of Forgery on the deed he/she makes and What is the position of a Notary/PPAT who commits the Crime of Money Laundering (TPPU) and/or the Crime of Forgery related to Court Decision Number 248/Pid. B/ 2022/ PN.Jkt.Brt. This research method uses a type of Normative Juridical research using a descriptive analytical approach to legislation. The data source uses secondary data sources using legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials with the use of library research data collection techniques and data collection tools in this study are document studies and interviews. The result of the research is that the Notary/PPAT can be indicated by the Crime of Money Laundering (TPPU)/Forgery if it is proven/proven to carry out activities of making fake authentic letters or falsifying letters, as if the letter is genuine and can harm others. Furthermore, a Notary/PPAT violating these provisions may be subject to civil, criminal, and administrative sanctions. Administrative sanctions include written warning, temporary dismissal, honourable dismissal, and dishonourable dismissal, which is adjusted to the act of violation committed by the Notary/PPAT itself. And Notary/PPAT who commits the Crime of Money Laundering (TPPU)/Forgery can be subject to all three existing sanctions, which can be subject to criminal sanctions that automatically apply, civil sanctions, namely compensation with a note that if the relevant party reports from the actions of the Notary/PPAT, and administrative sanctions that are adjusted to the losses caused by the Notary/PPAT, including written warnings, temporary dismissal, honourable dismissal, and dishonourable dismissal.